Perlindungan Hukum Jaminan Sosial Penempatan Pekerja Migran Indonesia di Luar Negeri Berdasarkan Konvensi dan UU No. 18 Tahun 2017 tentang Perlindungan Pekerja Migran Indonesia - Hesti Dwi Rela Susanti; Ferinzka Emeralda Putri (Universitas Muhammadiyah Jember, 2020)
This writing is based on the legal protection of Indonesian workers who are abroad, as a guarantee for a sense of trust and security in working in a foreign country, get clear legal protection, and to examine explicitly how social security for Indonesian Migrant Workers according to International Convention and the Act Number 18 of 2017 concerning Protection of Indonesian Migrant Workers. Using writing methods based on normative legal research, also known as doctrinal law research. Legal protection given to Indonesian Migrant Workers sought by the government for the creation of legal regulations that protect all activities of Migrant Workers who are Abroad. The government has the responsibility and obligation to safety and protect all its citizens wherever they are legally, so that their citizens have a sense of security of the right to work and there are no longer any cases that threaten the safety of Indonesian Migrant Workers.